NOTA BIOLÓGICA SÔBRE METACUTEREBRA APICALIS (GUÉRIN, 1829/38) (DIPTERA. CUTEREBRIDAE) - Forattini, Oswaldo P.; Lenko, Karol (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1959)
The authors report some ohservations on the time taken by pupal stage o f Metacuterebra apicalis (Diptcra, Cutcrchridac), a parasite of sylvan rodents of the genus Oryzomys. That time was found varying from 29 to 31 days. The species Oryzomys wavrini Thomas is reportecl as a host for the first time.